2008
DOI: 10.1088/0952-4746/28/4/007
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of atmospheric dispersion of radionuclides using an Eulerian–Lagrangian modelling system

Abstract: In this paper we present an atmospheric dispersion scenario for a proposed nuclear power plant in Pakistan involving the hypothetical accidental release of radionuclides. For this, a concept involving a Lagrangian stochastic particle model (LSPM) coupled with an Eulerian regional atmospheric modelling system (RAMS) is used. The atmospheric turbulent dispersion of radionuclides (represented by non-buoyant particles/neutral traces) in the LSPM is modelled by applying non-homogeneous turbulence conditions. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…where r a is the aerodynamic resistance; r b is the quasilaminar layer (viscous sublayer) resistance; and r s is the surface resistance (describing the resistance of the surface to the uptake/absorption/adsorption of the gas). The parameterizations of these three resistances in our study follows Brandt et al (2002).…”
Section: The Resistance Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…where r a is the aerodynamic resistance; r b is the quasilaminar layer (viscous sublayer) resistance; and r s is the surface resistance (describing the resistance of the surface to the uptake/absorption/adsorption of the gas). The parameterizations of these three resistances in our study follows Brandt et al (2002).…”
Section: The Resistance Methodsmentioning
confidence: 99%
“…where u grav is the gravitational settling velocity. According to Brandt et al (2002), the gravitational settling velocity can be calculated from the Stokes equation (small particles in the atmosphere experience a creeping flow, Reynolds number 1, that appears to change in time due to the larger scale turbulent eddies):…”
Section: The Resistance Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this particular accident at Fukushima, the Community Multi-scale Air Quality (CMAQ) model (Morino et al, 2011), the Lagrangian transport models HYSPLIT and FLEXPART with meteorological conditions provided by the Weather Research and Forecasting (WRF) model (Srinivas et al, 2012), and the WRF-Chem tracer model which directly couples the simulation of the chemistry and meteorology (Huh et al, 2012(Huh et al, , 2013) have been used. These studies, together with many previous studies for other events, have identified a number of meteorological variables that can significantly influence the atmospheric transport and ground deposition of radionuclides, including wind and rainfall (Basit et al, 2008;Mathieu et al, 2012;Takemura et al, 2011;Ten Hoeve and Jacobson, 2012;Yamauchi, 2012). For example, the study of Morino et al (2011) has shown that during the period from 11 to 30 March 2011, the amounts of 131 I and 137 Cs transported across the eastern boundary (downwind) of their domain are 6.52 × 10 16 Bq and 4.58 × 10 15 Bq, respectively; while those across the western boundary (upwind) are only 1.49 × 10 12 Bq and 1.13 × 10 7 Bq, respectively.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 95%